Arthroscopic debridement and lavage of a fetlock joint in a British blue calf. Issue 1 (6th November 2022) - Watson, Christopher; Cullen, Matthew; Stack, J. David
Abstract: A 3‐week‐old pedigree British blue bull, weighing 70 kg, presented with soft tissue swelling of the distal left forelimb, with a discharging sinus associated with a granulating wound (pressure sore). Involvement of the metacarpophalangeal joint was suspected. There were also granulating wounds on the dorsal aspect of both metacarpophalangeal joints and laterally on both tarsi. Radiography, arthrocentesis, arthroscopy and joint lavage were carried out under general anaesthesia and the external wounds were debrided and dressed. Intra‐articular antibiotics were given at the time of surgery and systemic antibiotics and anti‐inflammatories were given for 14 days afterwards. The calf made a good recovery and returned to normal function.